2010
DOI: 10.1007/s00520-010-0865-2
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender differences in symptom intensity and symptom clusters among patients with metastatic cancer

Abstract: In patients with advanced cancers, symptom patterns differ according to age and gender. Palliative interventions tailored for symptoms that are more prominent in specific patient subgroups may offer greater therapeutic benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 54 publications
14
113
6
1
Order By: Relevance
“…Nausea, vomiting and diarrhea were also symptoms where gender differences were observed [4,9,15,[17][18][19][20]. Throughout the studies that examined nausea and vomiting in relation to gender, all studies concluded that these two symptoms occurred more frequently in female advanced cancer patients [4,9,15,[17][18][19]. Donnelly et al also found that female gender was associated with greater severity of these symptoms [3].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nausea, vomiting and diarrhea were also symptoms where gender differences were observed [4,9,15,[17][18][19][20]. Throughout the studies that examined nausea and vomiting in relation to gender, all studies concluded that these two symptoms occurred more frequently in female advanced cancer patients [4,9,15,[17][18][19]. Donnelly et al also found that female gender was associated with greater severity of these symptoms [3].…”
Section: Resultsmentioning
confidence: 99%
“…As such, these findings suggest that health care professionals should take into consideration the multidimensionality of pain by combining emotional counseling with other treatments, especially for female patients. For nausea and vomiting, although the increased frequency seen in females in the advanced cancer population is generally agreed upon and this prevalence is also common to other disorders, its' mechanism is still uncertain [4,9,15,[17][18][19][20]. Symptoms such as dyspnea, decreased appetite, drowsiness, sleep problems, hoarseness, diarrhea, constipation and others were all found to have gender difference in experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cutoff was based on the findings that indicate cancer mortality rates are increasing in those aged older than 60 years 17 and is consistent with other large studies in this field. 18,19 Symptom Clusters Study. This prospective, longitudinal study was designed to identify symptom clusters and their effects on physical and psychological functioning of patients with metastatic disease.…”
Section: Study Samplesmentioning
confidence: 99%